Fair Value Accounting, Illiquid Assets, and Financial Stability - Mahieux, Lucas (Management Science, 2024)
In this paper, I analyze the joint design of capital requirements and fair value reporting rules for financial institutions with illiquid assets. I specifically examine how prudential regulation aimed at solving agency problems affects financial institutions’ incentives to use Level 2 versus Level 3 fair value reporting, as well as financial stability. Crucially, Level 3 reporting allows financial institutions to use their private information, whereas Level 2 fair values are only measured with public information. Interestingly, my analysis shows regulators may leave to financial institutions the discretion to report illiquid assets at Level 2 or Level 3. Financial institutions then report at Level 3 only if they have good private information about the assets’ quality. Moreover, prudential rules that only rely on Level 2 fair values may be efficient at solving agency problems within financial institutions but may also decrease financial stability. By contrast, prudential rules that leave to financial institutions the discretion to report illiquid assets at Level 2 or Level 3 while relaxing capital requirements may increase financial stability. This paper was accepted by Suraj Srinivasan, accounting. Funding: This work was supported by the H2020 European Research Council [Grant 669217]. Supplemental Material: The online appendix is available at https://doi.org/10.1287/mnsc.2023.4692 .